Биохимические фенотипы деревьев дуба черешчатого в связи с устойчивостью к листогрызущим насекомым и естественным отбором - Полякова, Л.В.; Гамаюнова, С.Г.; Журова, П.Т. (Фактори експериментальної еволюції організмів, 2014)
Aims. Biochemical properties of common oak (Quercus robur L.) many centuries trees (200–300 years old) and trees of young culture (55 years old) were studied. Methods. The contents of protein (PR) and some groups of second metabolites in leaves were determined. The main species of herbivores were Altica quercetorum and Erannis defoliaria. Results. The contents of PR and condensed tannins (CT) in leaves of centuries trees were more higher. Correlations between PR content and hydrolysable tannins (HT) in all cases of determinations were negative. According these correlations all trees of each forest stand were divided on three biochemical phenotypes. Conclusions. Each biochemical phenotype of tree was optimal as host-tree for different herbivore species. Correlation PR–HT was much higher for many-centuries trees. Young culture characterized with low level of this correlation. It is possible to speculate that trees with some deviation in these correlations can be more ease eliminated from forest trees stand during nature selection.

Key words: Quercus robur, biochemical phenotypes, herbivores.